Diversity and distribution of intertidal Microporella (Bryozoa: Cheilostomatida) from California - Chowdhury, Ismael A.; Di Martino, Emanuela; Lee, Hannah; Windecker, Claire C.; Craig, Sean (European Journal of Taxonomy, 2024)
Seven species of the cheilostome bryozoan genus Microporella were identified across 15 rocky intertidal sites spanning 940 km of the California coast, from Mill Creek in the Montereyan Pacific Transition Region north to Point Saint George in the Mendocinian Region. Colonies of Microporella were found encrusting boulders and mollusc shells. Among these species, three are new to science, namely Microporella dentata Chowdhury & Di Martino sp. nov., M. pauciperforata Chowdhury & Di Martino sp. nov. and M. rota Chowdhury & Di Martino sp. nov. Three other species, M. californica, M. setiformis, and M. umbonata have previously been recorded from other localities in California. Finally, Microporella neocribroides, originally described from off Kodiak Island, Alaska, and subsequently found in Hokkaido, Japan, was recorded in California for the first time. An additional new species, M. similis Chowdhury & Di Martino sp. nov., was identified through the re-examination of museum material previously attributed to M. cribrosa and M. californica. These newly acquired data allowed for a more comprehensive examination of the distribution of species, intraspecific variability, and potential predator-induced teratologies in certain species, thanks to the availability of numerous colonies from various sites and the re-examination of museum records. Altogether, this study increases the known Recent diversity of Microporella in California’s waters to a total of 18 species.